Metode Pembelajaran yang Diterapkan Mahasiswa Sastra Inggris pada Saat Pelaksanaan PPL Asistensi Mengajar - Sri Melani Ayu Shinta; Andang Saehu (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
PPL teaching assistance activities are held to involve students. In this teaching assistance activity, students are not limited to conveying knowledge to students but there are several things that educators must consider, one of which is the learning method. This study will discuss matters such as 1) analyzing learning methods, and 2). The effectiveness of the learning methods used, 3). Obstacles/challenges faced along with the solutions provided, 4). How to measure student understanding, 5). How to deal with students who have difficulty understanding lessons or studying. The method used in this research is a descriptive type of case study. This is to present the results of the analysis of English Literature students at the Islamic University of Sunan Gunung Djati Bandung when they carry out the integrated MBKM-fild work program, in August 2022. From the data obtained English Literature students who conduct fild work program use a lot of the lecture method. Then followed by using the method of discussion, and question and answer. The third position is the drill method. The last is simulation method, the experimental experience method, studying by learning, and task-based learning. The learning method is a way for educators to convey teaching materials to students. In the learning method itself, there are various methods. Starting from the lecture method, discussion, question and answer, demonstration, simulation, experimental experience, study tour, drill (practice), problem-solving, discovery, self-analysis, jigsaw method, and so on. However, from this research, the lecture method is the most widely used choice by English Literature students.